Synthesis of MoS2-TiO2 nanocomposite for enhanced photocatalytic and photoelectrochemical performance under visible light irradiation. (September 2018) - Mehta, Manan; Singh, Aadesh P.; Kumar, Sandeeep; Krishnamurthy, Satheesh; Wickman, Björn; Basu, Suddhasatwa
Abstract: In this work, we have prepared MoS2 nanoflakes modified TiO2 nanoparticles (MoS2 -TiO2 nanocomposite) with varying concentration of MoS2 (2.5–10 wt.%) by a two-step hydrothermal synthesis method involving specific preparation conditions for the TiO2 nanoparticles and MoS2 nanoflakes. The prepared samples were characterized by X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDX), and X-ray photoelectron spectroscopy (XPS) techniques. The photocatalytic activity of the pristine TiO2 nanoparticles and MoS2 -TiO2 nanocomposite samples were evaluated by examining the photocatalytic degradation of Rhodamine B (RhB). The photoelectrochemical activity of these samples were measured by performing solar water splitting experiments under visible light irradiation. It was observed that the MoS2 -TiO2 nanocomposite with 7.5 wt.% MoS2 exhibits highest photocatalytic and photoelectrochemical activity as it has the optimum amount of MoS2 nanoflakes which probably minimizes the recombination of photogenerated charge carriers as compared to other concentrations of MoS2 in MoS2 -TiO2 nanocomposite and pristine TiO2 nanoparticles. In addition, a rather high photocatalytic reaction rate constant was observed for MoS2 -TiO2 nanocomposite with 7.5 wt.% MoS2 nanoflakes. Highlights: TiO2 -MoS2 nanocomposite with varying concentration of MoS2 was prepared by two-step hydrothermal synthesis method. The photocatalytic activity of TiO2 -MoS2 nanocomposite was evaluated by examining degradation of Rhodamine B (RhB). PEC activity was determined by solar water splitting experiments. 7.5 wt.% MoS2 in TiO2 exhibits highest photocatalytic and photoelectrochemical activity.